Statics and Strength of Materials : an integrated presentation - Trathen, Roland H. (Wiley, 1954)
Some fundamental concepts - Bars under axial loading - The truss, simple connections - Statically determinate beams - Twisting of circular bars - Stress at a point and combined stresses - Strain at a point, stress-strain relations - Theories of failure for members subjected to biaxial stresses - Additional methods for determining beam deflections - Statically indeterminate structures - Beams-special problems - Columns - Dynamic and repeated loads - Forces in space - Supplementary problems - Appendix - Answers to problems.